2017
DOI: 10.1038/s41598-017-12071-6
|View full text |Cite
|
Sign up to set email alerts
|

Probing nanoscale damage gradients in ion-irradiated metals using spherical nanoindentation

Abstract: We discuss and demonstrate the application of recently developed spherical nanoindentation stressstrain protocols in characterizing the mechanical behavior of tungsten polycrystalline samples with ionirradiated surfaces. It is demonstrated that a simple variation of the indenter size (radius) can provide valuable insights into heterogeneous characteristics of the radiation-induced-damage zone. We have also studied the effect of irradiation for the different grain orientations in the same sample.Materials with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(10 citation statements)
references
References 83 publications
3
7
0
Order By: Relevance
“…the indentation stress and strain measures to convert the corrected P − h response into an indentation stress-strain curve (see reference [43] for more details). The obtained indentation stress-strain curves from multiple grain interiors on the reference sample were found to be continuous and similar, as displayed in figure 2(c), which are consistent with previous studies on recrystallized tungsten [43,73]. It should be noted that the stress measure we use here is called indentation stress, which is different from the yield stress used in a uniaxial tensile/compression test.…”
Section: Mechanical Testing By Nanoindentationsupporting
confidence: 88%
“…the indentation stress and strain measures to convert the corrected P − h response into an indentation stress-strain curve (see reference [43] for more details). The obtained indentation stress-strain curves from multiple grain interiors on the reference sample were found to be continuous and similar, as displayed in figure 2(c), which are consistent with previous studies on recrystallized tungsten [43,73]. It should be noted that the stress measure we use here is called indentation stress, which is different from the yield stress used in a uniaxial tensile/compression test.…”
Section: Mechanical Testing By Nanoindentationsupporting
confidence: 88%
“…The origins of this, for tests all performed at the same temperature, is solid solution hardening, which increases with the square root of the solute concentration [60,61]. The yield strength also increases monotonically with irradiation level for all FeCr materials measured, which has been previously observed in other irradiated materials [54,62].…”
Section: Indentation Stress-strain Curvessupporting
confidence: 75%
“…Using the protocols described in Section 2.3 [54,55], indentation stress-strain (ISS) curves were calculated for the indents made with the 5.12 µm spherical tip (Figure 8). The effects of pop-ins are clearly seen, with large elastic stresses in the ISS response before the flow portion proceeds at much lower stress levels.…”
Section: Indentation Stress-strain Curvesmentioning
confidence: 99%
“…Furthermore, it is necessary to compute the ISE for the CSM top-down method, but this effect is reduced in the OCS method by virtue of the increase in the irradiation-induced defects for indents in the peak damage region, while the ISE remains an important factor in the low or zero dose regions. Other studies have shown the ISE pop-ins are the result of difficulty in activating dislocations sources (e.g., Frank-Read sources) [26,27], but for the inclined nanoindentation studies presented herein (i.e., the indentations in the regions in and adjacent to the peak of the hardness curve), there is greater activation due to the higher number of irradiation induced dislocation sources [28]. This diminishes the ISE in the highly irradiated regions and provides for greater correlation between the model and experiments after the use of ISE corrections in the virgin material.…”
Section: Discussionmentioning
confidence: 59%